NiCo2O4 spinel for efficient toluene oxidation: The effect of crystal plane and solvent. (November 2020) - Niu, Jianrui; Liu, Haobin; Zhang, Yiyuan; Wang, Xin; Han, Jing; Yue, Zihan; Duan, Erhong
Abstract: Spinel oxides, e.g., NiCo2 O4, is a promising catalyst for the catalytic oxidation of toluene. Understanding and designing versatile NiCo2 O4 spinel is important for low-temperature toluene oxidation. Here, we investigated the surface-characteristic-dependent degradation activity of NiCo2 O4 crystals through experiment and characterization. NiCo2 O4 nanosheet using ethanol as solvent (named E–NiCo2 O4 ) exposing 110 crystal planes exhibited the lowest temperature toluene oxidation. The T99 of toluene conversion was 256 °C, which is much lower than that of NiCo2 O4 nanosheet using ethylene glycol as solvent (named EG–NiCo2 O4 ), NiCo2 O4 octahedron (named O–NiCo2 O4 ) and NiCo2 O4 truncated octahedron (named TO–NiCo2 O4 ). Characterization using various techniques such as XRD, TEM, BET, XPS, H2 -TPR and CO2 -TPD showed that Co 3+ and surface adsorbed oxygen (Osur ) enriched surface, excellent redox properties and effective diffusion of the reaction product reasonably explain the enhancement in catalytic activity over the E–NiCo2 O4 . The research reveals that the effect of specific crystal planes and solvent was the key factor to govern the activity of low-temperature toluene oxidation. Graphical abstract: Image 1 Highlights: The crystal planes can adjust the surface chemical properties of NiCo2 O4 . Solvent will affect the amount of high valence metal. The Osur was the active component. The amount and redox properties of Co 3+ will affect continuously supply of Osur . The catalyst showed good stability even when water was introduced the reaction.